The Influence Of Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence On Employee Performance Through Work Ethics - Asmaraningtyas, Lussy Widia; Setiyono, Wisnu Panggah (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines the influence of intellectual, emotional, and spiritual intelligence on employee performance, with work ethics as a mediating variable. Using a quantitative causal-associative approach, the research involved 133 LP3I Sidoarjo alumni (2020–2024) working across various regions in East Java, selected from a population of 200 using Slovin’s formula. Data were analyzed through Partial Least Squares (PLS) with validity, reliability, and model evaluation tests. Results indicate that all forms of intelligence and work ethics have significant positive effects on performance, with work ethics mediating these relationships. The findings underscore the importance of intelligence and work ethics as foundations for optimal performance and long-term organizational success